Urolithin A and nicotinamide riboside differentially regulate innate immune defenses and metabolism in human microglial cells - Madsen, Helena Borland; Navarro, Claudia; Gasparini, Emilie; Park, Jae-Hyeon; Li, Zhiquan; Croteau, Deborah L.; Bohr, Vilhelm A. (Frontiers in Aging Neuroscience, 2024)
IntroductionDuring aging, many cellular processes, such as autophagic clearance, DNA repair, mitochondrial health, metabolism, nicotinamide adenine dinucleotide (NAD+) levels, and immunological responses, become compromised. Urolithin A (UA) and Nicotinamide Riboside (NR) are two naturally occurring compounds known for their anti-inflammatory and mitochondrial protective properties, yet the effects of these natural substances on microglia cells have not been thoroughly investigated. As both UA and NR are considered safe dietary supplements, it is equally important to understand their function in normal cells and in disease states.MethodsThis study investigates the effects of UA and NR on immune signaling, mitochondrial function, and microglial activity in a human microglial cell line (HMC3).ResultsBoth UA and NR were shown to reduce DNA damage-induced cellular senescence. However, they differentially regulated gene expression related to neuroinflammation, with UA enhancing cGAS-STING pathway activation and NR displaying broader anti-inflammatory effects. Furthermore, UA and NR differently influenced mitochondrial dynamics, with both compounds improving mitochondrial respiration but exhibiting distinct effects on production of reactive oxygen species and glycolytic function.DiscussionThese findings underscore the potential of UA and NR as therapeutic agents in managing neuroinflammation and mitochondrial dysfunction in neurodegenerative diseases.